Mid- to long-term clinical outcomes of modified technique skip-level titanium plate fixation in cervical laminoplasty compared to continuous fixation - Shuo Feng; QiRui Zhu; Yang Sun; ZiYao Ding; Zhe Zhuang; Heng-Heng Yu; Ma-Ji Sun; Feng Yuan (Journal of Orthopaedic Surgery and Research)
Abstract Purpose To compare the efficacy and safety of skip titanium plates combined with adjacent spinous process suture suspension versus continuous titanium plate fixation in cervical laminoplasty. Methods A retrospective analysis of 125 patients (62 men, 63 women, average age 60.9 ± 10.4 years) with multilevel cervical spondylotic myelopathy who had cervical laminoplasty with Arch titanium plate fixation from January 2012 to March 2024 in our hospital was done. Patients were stratified into two cohorts based on the fixation technique: Group A (n = 64): Modified technique of skip-level titanium plate fixation (Arch titanium plates at C4 and C6 levels combined with adjacent spinous process suture suspension)Group B (n = 61): Continuous plating (Arch titanium plates applied sequentially from C3 to C7).The comparative analysis focused on perioperative parameters (operative duration, intraoperative blood loss, length of hospital stay), economic factors (hospital costs), and various clinical indicators. Results The average follow up period was (73.0 ± 38.4) months. Both groups showed no significant differences in gender, age, and disease duration (P > 0.05). Group A had lower hospitalization costs, intraoperative blood loss, operation time, and postoperative hospital stay compared to Group B (P < 0.05). Postoperatively, both groups had significant improvements in JOA scores and NDI (P < 0.005), but there were no significant differences in postoperative scores and improvement rates between the two groups (P > 0.05). At 3 months postoperatively and at the last follow-up, the C2-7 Cobb angle and cervical curvature index decreased compared to preoperative values (P < 0.05), with a significant difference in the C2-7 Cobb angle at the last follow-up (P < 0.05). The sagittal diameter of the spinal canal from C3 to C7 significantly increased (P < 0.05), but there were no significant differences in the improvement of C3, C5, and C7 between the two groups (P > 0.05). At 3 months postoperatively, the opening angles of the C4 and C6 laminae in Group A were smaller than those in Group B (P < 0.05), but there were no significant differences at the last follow-up (P > 0.05). The healing of the C4 and C6 laminae in Group B was superior to that in Group A (P < 0.05), but there were no differences in healing at the last follow-up (P > 0.05). The incidence of axial symptoms was similar (10.9% in Group A and 14.8% in Group B, P = 0.523). Conclusions During C3-7 laminoplasty, the clinical efficacy of the method combining mini titanium plate fixation (at C4 and C6) with suture fixation is comparable to that of continuous fixation. Moreover, it has an advantage in cost control.